On two new paraonids (Annelida, Paraonidae) from Bahía de los Angeles, Gulf of California, Mexico - León-González, Jesús Angel De; Díaz-Castañeda, Victoria; Tovar-Hernández, María Ana (Zootaxa, 2025)
Two new species of Paraonidae (Annelida) belonging to the genera Aricidea (Acmira) Hartley, 1981 and Paradoneis Hartman, 1965, are described from soft bottoms of Bahía de Los Angeles, Gulf of California. Aricidea (Acmira) blackei sp. nov. is characterized by having a short, digitiform antenna with a discrete swollen base; by possessing notopodial postchaetal lobes in prebranchial and branchial region, changing gradually in size and shape from the first two chaetigers to the last pair of branchiae; last pair of branchiae being shorter than the rest; and by having curved hooks with a very strong hood and a fragile arista. Paradoneis mackiei sp. nov. is characterized by the presence of lyrate notochaetae with tines of different thickness along body, showing an evident increament in size from anterior to posterior end. Identification keys to all species of Aricidea (Acmira) and Paradoneis are included.